Linking Rheology and Printability for Dense and Strong Ceramics by Direct Ink Writing - Amin M’Barki (Nature Portfolio, 2017)
Abstract Direct ink writing of dense and strong ceramic objects remains an important open challenge. We develop a universal dimensionless criterion for printing such objects. Boehmite, an Al2O3 precursor, was used to assess the rheological properties leading to dense structures in ceramics manufactured by direct ink writing. Boehmite suspensions undergo time dependent gelation, thus providing a rheological laboratory of flow behaviours that can be correlated with printability requirements. We measured the evolution of rheological properties over several days and quantified the deformation of simple printed shapes at different aging times. We then identified the relevant physical parameters leading to printable suspensions. We defined a dimensionless number, Ξ, based on measured rheological properties, that predicts deformation of the printed object and determines the printability criterion. An important difference with this criterion is that Ξ necessarily accounts for capillary forces and gravitational slumping. We show that boehmite inks reach a printed shape fidelity > 90% when Ξ > 1, and that Al2O3 bars printed under these conditions can be sintered to 97% density, without printing defects, and have flexural strengths (500–600 MPa) competitive with commercial aluminas. Using Ξ, researchers can rationally design inks for printing dense materials by tailoring their rheological properties such that Ξ ≈ 1.